Prevalence and associated risk factors for failed obstetric fistula repair in East African countries: A systematic review and meta-analysis - Neway Ejigu; Kenbon Seyoum; Chala Kene; Degefa Gomora; Shelema Mengistu; Girma Geta; Derese Eshetu; Shimelis Tadesse; Telila Mesfin; Yohannes Tekalign; Daniel Atlaw (SAGE Open Medicine, 2023)
Objective: Obstetric fistula repair failure is a combination of unsuccessful fistula closure and/or incontinence following a successful closure. There is an inconsistent finding on the failure of obstetric fistula repair in East Africa. Therefore, this systematic review and meta-analysis aimed to determine the pooled prevalence of failed obstetric fistula repair and its associated factors among women who have undergone fistula repair in East Africa. Methods: This systematic review and meta-analysis were written following the PRISMA guideline protocol. A web-based electronic search of PubMed, Google Scholar, and HINARI was performed to find primary studies. Additional articles were searched by cross-referencing references. A random-effects model was used to estimate the pooled prevalence of failed obstetric fistula repair. The heterogeneity of studies was weighed using I 2 test statistics. Publication bias was assessed by Eggers and funnel plot test. Results: The 16 studies that met the inclusion criteria for this systematic review and meta-analysis of failed obstetric fistula repair were included. Nonetheless, one study was used for factor analysis but not in pooled prevalence analysis. The pooled prevalence of obstetric fistula repair failure in East Africa was 26.89% (95% confidence interval: 21.71, 32.07). Labor duration > 48 h (Pooled odds ratio = 2.46; 95% confidence interval 1.58, 3.82), fistula size >3 cm (Pooled odds ratio = 3.92; 95% confidence interval 2.19, 7.05), previous fistula repair (Pooled odds ratio = 3.20; 95% confidence interval 1.94, 5.29), Goh Type 4 fistulas (Pooled odds ratio = 6.07; 95% confidence interval 2.50, 14.75), completely destructed urethra (Pooled odds ratio = 3.35; 95% confidence interval 1.69, 6.65), and severe vaginal scaring (Pooled odds ratio = 3.89; 95% confidence interval 1.99, 7.62) were significantly associated with obstetric fistula repair failure. Conclusions: One in four women with obstetric fistula repair experienced repair failure. To fight the problem The Ministry of Health in every part of the country, in collaboration with obstetric care providers, shall intervene on factors affecting obstetric fistula repair failure to reduce or prevent the failure of obstetric fistula repair.